A safe and effective vaccine against bovine leukemia virus - Suárez Archilla, Guillermo; Gutiérrez, Gerónimo; Camussone, Cecilia; Calvinho, Luis; Abdala, Alejandro; Alvarez, Irene; Petersen, Marcos; Franco, Lautaro; Destefano, Gabriel; Monti, Gustavo; Jacques, Jean-Rock; Joris, Thomas; et al. (Frontiers in Immunology, 2022)
Previous attempts to develop a vaccine against bovine leukemia virus (BLV) have not been successful because of inadequate or short-lived stimulation of all immunity components. In this study, we designed an approach based on an attenuated BLV provirus by deleting genes dispensable for infectivity but required for efficient replication. The ability of the vaccine to protect from natural BLV infection was investigated in the context of dairy productive conditions in an endemic region. The attenuated vaccine was tested in a farm in which the prevalence rose from 16.7% in young cattle at the beginning of the study to more than 90% in adult individuals. Sterilizing immunity was obtained in 28 out of 29 vaccinated heifers over a period of 48 months, demonstrating the effectiveness of the vaccine. As indicated by the antiviral antibody titers, the humoral response was slightly reduced compared to wild-type infection. After initial post-vaccination bursts, the proviral loads of the attenuated vaccine remained most frequently undetectable. During the first dairy cycle, proviral DNA was not detected by nested-PCR in milk samples from vaccinated cows. During the second dairy cycle, provirus was sporadically detected in milk of 2 vaccinated cows. Forty-two calves born from vaccinated cows were negative for proviral DNA but had antiviral antibodies in their peripheral blood. The attenuated strain was not transmitted to sentinels, further supporting the safety of the vaccine. Altogether, these data thus demonstrate that the vaccine against BLV is safe and effective in herd conditions characterized by a very high incidence. This cost-effective approach will thus decrease the prevalence of BLV without modification of production practices. After facing a series of challenges pertaining to effectiveness and biosafety, the vaccine is now available for further large-scale delivery. The different challenges and hurdles that were bypassed may be informative for the development of a vaccine against HTLV-1.